Multimodal Therapeutic Approach of Cytokine Release Syndrome Developing in a Child Given Chimeric Antigen Receptor-Modified T Cell Infusion. (January 2020) - Bottari, Gabriella; Merli, Pietro; Guzzo, Isabella; Stoppa, Francesca; Ruggeri, Annalisa; Di Nardo, Matteo; Del Bufalo, Francesca; Galaverna, Federica; Corrado, Cecchetti; Locatelli, Franco
Abstract : Objectives: To describe a pediatric case of cytokine release syndrome secondary to chimeric antigen receptor-modified T cells associated with acute respiratory distress syndrome. Design: Case report. Setting: PICU. Patients: A 14-year-old boy with refractory B cell precursor acute lymphoblastic leukemia given chimeric antigen receptor cells developed severe cytokine release syndrome 7 days after the drug product infusion with progressive respiratory failure. He was admitted to PICU with a clinical picture of acute respiratory distress syndrome, requiring mechanical ventilation, and secondary hemophagocytic lymphohistiocytosis. Interventions: Hemoadsorption with cartridge column (Cytosorb) in combination with continuous renal replacement therapy was associated to the anti-cytokine therapy (tocilizumab, a monoclonal antibody targeting interleukin-6 receptor). Measurements and Main Results: Decrease of the inflammatory biomarkers (ferritin, interleukin-6, interleukin-10) in the first 96 hours associated with a progressive improvement of acute respiratory distress syndrome (PaO2 /FIO2 ratio) 7 day after the start of the multimodal treatment. Conclusions: This case suggests that hemoadsorption with cartridge column in combination with continuous renal replacement therapy and tocilizumab is safe and potentially effective in pediatric patients with severe cytokine release syndrome.